Exploring Plagiarism Behavior in Higher Education - ., Amsal; Supratikta, Hadi; Sulistyono, Djoko; ., Purwadi; Wibowo Budi Santoso, Catur (KnE Social Sciences, 2024)
This study aims to explore plagiarism behavior in higher education. This study employed a qualitative method with a case study design using the reflective notes technique to collect data from the participants. The data were collected through online submission. The authors, at this moment, employed a qualitative method by assigning the participants to write reflective notes to obtain the true responses to various questions. The approach used in this study is a case study approach to understand the object studied. Ten students of Universitas Negeri Makassar were invited to participate in this study, but only six met the valid reflective notes. The study found that students have different views on plagiarism behavior. Some problems highlighted in this study related to plagiarism behavior, such as lack of training in proper writing techniques, academic dishonesty, lack of access to library resources, lack of admiration for fellow writers, and little or no consequence for plagiarism cases. Keywords: plagiarism behavior, higher education, case study, reflective notes technique